Real‐time assessment of heart rate variability and loss of control eating in adolescent girls: A pilot study. Issue 2 (24th September 2015) - Ranzenhofer, Lisa M.; Engel, Scott G.; Crosby, Ross D.; Haigney, Mark; Anderson, Micheline; McCaffery, Jeanne M.; Tanofsky‐Kraff, Marian
ABSTRACT: Objective: Studying physiologic underpinnings of loss‐of‐control (LOC) eating may inform its etiology and contribute to intervention efforts. We therefore examined temporal relationships between autonomic indices [heart rate (HR), heart rate variability (HRV)] and LOC‐eating in the natural environment. Method: For two days, adolescents ( n = 17, 14.77 ± 1.55 years, BMI‐Z 2.17 ± 0.48) with LOC‐eating reported on LOC using an electronic device while HR and HRV were assessed continuously using Holter monitoring. Results: Higher HR and lower HRV in the 30‐minutes before eating were significantly associated with LOC‐eating overall ( p's < 0.001) and at the within‐participants level ( p's < 0.001), but not at the between‐participants level ( p's > 0.44). Examined categorically, HR was significantly higher, and HRV significantly lower, prior to high‐LOC compared to low‐LOC episodes ( p's < 0.001). Discussion: This pilot study suggests that LOC‐eating may involve physiologic underpinnings. Additional research with larger samples is needed to further investigate this phenomenon. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:199–203).